Visual function abnormalities in Arnold-Chiari syndrome: Analysis of two cases (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To analyze clinical manifestations of visual function abnormalities in Arnold-Chiari syndrome.Material and Methods: Two patients with Arnold-Chiari syndrome (ACS) were under our observation at SI “The Filatov Institute of Eye Diseases and Tissue Therapy of the National Academy of Medical Sciences of Ukraine” and Eye Microsurgery Center, Multipurpose Medical Center, Odesa National Medical University. They underwent general clinical eye examinations.Results: We reviewed the cases of two patients with ACS. Major manifestations of the disease and the potential for treatment for preserving visual functions were determined.Conclusion: Taking a comprehensive approach to medical issues (especially those related to comorbid conditions) was always important. There are several ophthalmological issues that require consultations with neuropathologists and neurosurgeons for making a correct diagnosis and starting a subsequent treatment early. The cases presented showed that possible ACS manifestations may include e.g., strabismus and papilledema. Knowing these manifestations is a prerequisite for solving the diagnostic and treatment issues of the disease. There is no specific pathognomonic clinical sign or group of symptoms for the clinical diagnosis of ACS, and the disease can be diagnosed only by neuroimaging. Early identification of these ocular abnormalities allows suspecting and detecting this malformation early. Comprehensive treatment over many years can stabilize visual functions in patients with ACS.
Keywords: Arnold-Chiari syndrome; head MRI; optic nerve; neuritis; comprehensive treatment